2021
DOI: 10.1126/science.abl3771
|View full text |Cite
|
Sign up to set email alerts
|

Time-of-flight 3D imaging through multimode optical fibers

Abstract: Time-of-flight (ToF) 3D imaging has a wealth of applications, from industrial inspection to movement tracking and gesture recognition. Depth information is recovered by measuring the round-trip flight time of laser pulses, which usually requires projection and collection optics with diameters of several centimetres. In this work we shrink this requirement by two orders of magnitude, and demonstrate near video-rate 3D imaging through multimode optical fibres (MMFs) -the width of a strand of human hair. Unlike c… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
61
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 109 publications
(62 citation statements)
references
References 47 publications
1
61
0
Order By: Relevance
“…Averaging the power-ratio over all output locations yields the mean power-ratio p r . When our inverter is matched with an ideal fibre, the mean power-ratio of reimaged points p r = 0.74, a value comparable with the typical power-ratio for state-of-the-art serial wavefront shaping through MMFs [16,17].…”
Section: Looking Through Ideal Mmfsmentioning
confidence: 86%
See 2 more Smart Citations
“…Averaging the power-ratio over all output locations yields the mean power-ratio p r . When our inverter is matched with an ideal fibre, the mean power-ratio of reimaged points p r = 0.74, a value comparable with the typical power-ratio for state-of-the-art serial wavefront shaping through MMFs [16,17].…”
Section: Looking Through Ideal Mmfsmentioning
confidence: 86%
“…A key characteristic of our proposed fibre-inverter imaging system is the spectral bandwidth over which light can be unscrambled. The bandwidth of the TM of an MMF, ∆λ fib , defines the range of wavelengths over which the same TM is valid [17]. Assuming that chromatic dispersion is negligible compared to spatial mode dispersion, ∆λ fib can be derived by considering the optical path length difference between a ray travelling at the critical angle of total internal reflection versus a ray travelling 'straight through', parallel to the central fibre axis, yielding…”
Section: Spectral Bandwidthmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, recent reports have shown that the field of MMFs endoscopy can greatly benefit of Fourier plane-based approaches. [23,31,44] In this respect, the complex coupling between periodic plasmonic structures and the MMF's randomness can be harnessed by defining and holding a specific work point on the dispersion diagram (Figure 3E), setting the stage for endoscopic approaches based on EOT. This concept is shown in this work in a fiber optic featuring two orthogonal plasmonic nanogratings, and could be extended to ideally any type of photonic structures on the fiber facet, including dielectric metasurfaces.…”
Section: Discussionmentioning
confidence: 99%
“…In combination with time-of-flight detection, MMF-based endoscopes can nowadays also offer depth-perception in macroscopic three-dimensional scenes. Such far-field holographic endoscopes look set to further expand the range of applications within the biomedical and industrial inspection domains [183].…”
Section: Statusmentioning
confidence: 99%